Muscular strength and skeletal muscle mass in 511 physically independent older women aged 60–88 years - Kassiano, Witalo; Costa, Bruna; Nunes, João Pedro; Cyrino, Letícia T. [UNESP]; Nascimento, Matheus A. [UNESP]; Tomeleri, Crisieli; Antunes, Melissa; Gobbo, Luís A. [UNESP]; Ribeiro, Alex S.; Coelho-e-Silva, Manuel J.; Silva, Analiza M.; Sardinha, Luís B.; et al. (Elsevier, 2022)
Although one-repetition maximum (1RM) and lean soft tissue (LST) are the most common measures to assess muscular strength and skeletal muscle mass in older adults, reference data is still missing. Therefore, the present study aimed to produce reference values for the 1RM tests and LST in physically independent older women. Furthermore, the effect of age and body segment on these outcomes was examined. Five hundred and eleven older women aged 60–88 years participated in the present study. The 1RM tests were performed on chest press, leg extension, and preacher curl exercises. Dual-energy X-ray absorptiometry exams were used to determine total and segmental LST. The 1RM and LST average values: chest press = 44.0 ± 11.1 kg, leg extension = 48.8 ± 11.8 kg, preacher curl = 21.6 ± 5.4 kg; trunk LST = 19.0 ± 2.7 kg, lower-limbs LST = 12.5 ± 1.9 kg, upper-limbs LST = 4.0 ± 0.7 kg, appendicular LST = 16.6 ± 2.6, total LST = 38.5 ± 5.2 kg. The age-related declines in 1RM chest press and leg extension were higher than in preacher curl. The present study provides reference values for 1RM of different body segments and total and segmental LST in older women. In addition, our results revealed a reduction of muscular strength and LST with increasing age, and the magnitude of the age-related strength reduction depends on the body segment analyzed.
Keywords: Aging; Dynapenia; Fragility; Mortality; Resistance exercise; Sarcopenia